Musculoskeletal Metastases Management: The Interventional Radiologist's Toolbox - Mastier, Charles; Gjorgjievska, Ana; Thivolet, Arnaud; Bouhamama, Amine; Cuinet, Marie; Pilleul, Franck; Tselikas, Lambros; de Baère, Thierry; Deschamps, Frederic (Seminars in Interventional Radiology, 2018)
The prevalence of patients with painful bone metastases is constantly increasing. This is related to the rising incidence of cancer and increasing life expectancy of patients with metastatic stage. Advances in imaging and development of percutaneous techniques have gradually allowed offering minimally invasive acts on these metastases: cementing, vertebral augmentation, osteosynthesis, percutaneous thermal ablation, neurolysis, embolization. The purpose of this article is to present the main tools available to date for the interventional radiologist so that each participant can understand their functioning, indications, and limits.
Keywords: interventional radiology; metastases; cementoplasty; percutaneous ablation